Genomics Armed With Diversity Leads the Way in Brassica Improvement in a Changing Global Environment - Mohd Saad, Nur Shuhadah; Severn-Ellis, Anita A.; Pradhan, Aneeta; Edwards, David; Batley, Jacqueline (Frontiers in Genetics, 2021)
Meeting the needs of a growing world population in the face of imminent climate change is a challenge; breeding of vegetable and oilseed Brassica crops, is part of the race in meeting these demands. Available genetic diversity constituting the foundation of breeding is essential in plant improvement. Elite varieties, land races and crop wild species are important resources of useful variation and are available from existing genepools or genebanks. Conservation of diversity in genepools, genebanks and even in the wild is crucial in preventing the loss of variation for future breeding efforts. In addition, the identification of suitable parental lines and alleles is critical in ensuring the development of resilient Brassica crops. During the past two decades an increasing number of high quality nuclear and organellar Brassica genomes have been assembled. Whole genome re-sequencing and the development of pan-genomes are overcoming the limitation of a single reference genome and provide the basis for further exploration. Genomic and complementary omic tools such as microarrays, transcriptomics, epigenetics and reverse genetics facilitate the study of crop evolution, breeding histories, as well as the discovery of loci associated with highly sought after agronomic traits. Furthermore, in genomic selection predicted breeding values based on phenotype and genome-wide marker scores allow the preselection of promising genotypes, enhancing genetic gains and substantially quickening the breeding cycle. It is clear that genomics, armed with diversity, is set to lead the way in Brassica improvement, however a multidisciplinary plant breeding approach that includes phenotype x genotype x environment interaction will ultimately ensure the selection of resilient Brassica varieties ready for climate change.